อิทธิพลของอำนาจต่อพฤติกรรมเพื่อผลประโยชน์ส่วนตัว: การศึกษาอิทธิพลการป้องปรามของการรับรู้การถูกตรวจสอบเป็นตัวแปรกำกับ - ติณณ์ โบสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The purpose of this research was to investigate the influence of power on self-interested behavior and the moderating role of perceived accountability. One hundred and two Chulalongkorn University undergraduates were asked to answer a questionnaire via Google forms to assess their moral identity as a control variable. After two weeks, they were assigned to different power-perceived accountability conditions by using moral identity as matched groups factorial design to ensure nonsignificant difference between the moral identity scores in each condition. Later, the participants were tasked to complete a series of questionnaires and a group activity to measure their self-interested behavior. The study revealed that participants in the high power condition felt significantly more powerful than participants in the low power condition. There was no significant difference in perceived accountability between participants in the high perceived accountability condition, the low perceived accountability condition, and no perceived accountability condition. There was no significant interaction between the effects of power and perceived accountability on self-interested behavior. Moreover, the results showed that there was no significant main effect of power and perceived accountability.